Molecular chains of coordinated dimolybdenum isonicotinate paddlewheel clusters. Issue 29 (28th May 2019) - Li, Minyuan M.; Claire, F. James; Solomos, Marina A.; Tenney, Stephanie M.; Ivanov, Sergei A.; Siegler, Maxime A.; Kempa, Thomas J.
Abstract : Linear molecular chains of coordinated dimolybdenum isonicotinate clusters. Abstract : A growing focus on the use of coordination polymers for active device applications motivates the search for candidate materials with integrated and optimized charge transport modes. We show herein the synthesis of a linear coordination polymer comprised of Mo2 (INA)4 (INA = isonicotinate) metal–organic clusters. Single-crystal X-ray structure determination shows that this cluster crystallizes into one-dimensional molecular chains, whose INA-linked Mo2 cores engage in alternate axial and equatorial binding motifs along the chain axis. Electron paramagnetic resonance spectra, absorption spectra, and density functional theory calculations show that the aforementioned linear coordination environment significantly modifies the electronic structure of the clusters. This work expands the synthetic foundation for assembly of coordination polymers with tailorable dimensionalities and charge transport properties.